The Development of Word Square Media to Teach English Vocabulary for University Students - Budiarti, Desi; Suhono, Suhono; A. Hasyim, Umar Alfaruq; Hidayah, Yayuk; Sari, Yeasy Agustina (Bulletin of Science Education, 2024)
The article discusses the development of word square media in learning vocabulary for students. RnD model of researchers according to ADDIE. This study is a data analysis technique with descriptive analysis. Used to analyze data from questionnaire calculations and the results of interviews conducted. So that the data used in the study are grouped into 2, namely qualitative and quantitative data. Then it is analyzed descriptively to determine the suitability and quality of the product developed. The results of the research conducted obtained the results that word square media in learning vocabulary in students is very feasible to use. This is evidenced by the results of media expert validation by obtaining an average percentage result of 89.23% with the criteria of "very worthy". And it is also proven by the results of media trials with 19 students with the results of the evaluation of the developed word square media obtaining an overall score percentage of 86.63% with the criteria of "very worthy". Based on the results of data acquisition, it shows that word square media in learning vocabulary in students is very feasible to be used in the process of teaching English vocabulary. Keywords: Word Square Media, Teach Vocabulary, Development Media